Surgical management of Basal cell carcinomas (BCC) of the Head and Neck - Tawfique, Saleh A. (Sulaimani Journal for Pure and Applied Sciences, 2013)
Ninety six consecutive cases of BCC of the face and head and neck were managed during 8 years. 51 patients were female and the rest were male. The average age of presentation was 64Years. The size of majority of lesions (85%) were less than 10mm. Lesions appeared mainly on mid face around the nose, inner canthus and forehead. 10.5% had multiple lesions on presentation. All lesions were managed surgically by total excision of the lesions with 5mm free healthy skin margin and the defect reconstructed simultaneously by various types of local or distant skin flaps. The effectiveness of this procedure was 94% cure rate. The average follow up was 2 years (9-36 months). Ten patients(10.4%) required second surgical resection as they developed recurrence at the site of primary resection. Eleven patients (11.4%) showed another lesion on the face during follow up period. Surgical resection and primary reconstruction of BCCs of the head and neck are highly recommended and give good success and high percentage (around 94%) of cure rate. Long term follow up is recommended as new lesions or recurrence may appear years after management.
Keywords: BCC; skin cancer; surgical management Abbreviations BCC Basal cellcarcinoma L A local anesthesia G A general anesthesia EDC electrodessication and Curettage